Incidence of skin diseases diagnosed in a public institution: Comparison between 2003 and 2014 - Miguel, Livia Maria Zanardi [UNESP]; Rocha, Bruna [UNESP]; Jorge, Marilia Formentini Scotton [UNESP]; Miot, Hélio Amante [UNESP] (My University, 2017)
Epidemiology of diseases is influenced by population socio-demographic circumstances. Therefore it can be modified along the time. There are no studies exploring epidemiological transition in dermatology. This study investigated the incidence of dermatoses in new patients from a Brazilian country town public service in 2003 and 2014. There was a significant increase in the incidence of sexually transmitted diseases, leprosy, melasma, pruritus and hidradenitis suppurativa. However, a prominent reduction in scheduling of appointments for surgeries of benign lesions, drug reactions, urticaria and superficial mycoses was detected. The identification of epidemiological trends guides the dimensioning of health system and professional qualification policies.
Keywords: Demographic transition; Dermatology; Diagnosis; Epidemiology; Health transition; Incidence